Challenges posed to leadership: systematic review based on the relationships between curricular autonomy and teachers’ well-being - Lima, Louise; de Oliveira Martins, Alcina; Estrela, Elsa; Duarte, Rosa Serradas (Frontiers in Education, 2024)
IntroductionThis study is part of a cross-cutting and interdisciplinary funded research project involving researchers from different areas - education, sociology and psychology, which aims to contribute to deepening existing knowledge about the relationship between autonomy and curricular flexibility and teacher involvement and well-being. The study presented in this article is justified by the gap found in a Systematic Literature Review carried out in the context of the aforementioned research project. This research aims to understand the challenges posed to leadership based on the relationship between Portuguese educational policies within the scope of Autonomy and Curricular Flexibility developed since 2016 and teacher well-being. To this end, the research is based on the following question: What challenges do leaders face in promoting a school culture in a context of innovation and inclusion?MethodsThis article focuses on a systematic review of reports, recommendations, opinions and independent studies produced in the context of the development of autonomy and curricular flexibility policies in Portugal, published between 2015 and 2023. The selection of documents took into account the websites of the Ministry of Education in Portugal, the National Education Council, all the Teachers’ Unions in Portugal and Transnational Organizations.ResultsThe results show that leadership practices based on a collaborative approach and policies that favor teacher autonomy were associated with improved teacher well-being and the development of inclusive pedagogical practices. However, bureaucratization and work overload continue to be significant challenges in teachers’ daily lives. It was also found that the practices of pedagogical leaders can promote innovation and inclusion, requiring continuous institutional support.DiscussionThe results point to the fact that fostering an inclusive and innovative school culture requires leaders to adopt policies that value teacher well-being and promote opportunities for ongoing training. These results are in line with previous research that also points to the importance of a collaborative and supportive environment. The study is a starting point for further research into the relationship between curricular autonomy and teacher well-being.